From health plan companies to international insurance companies: changes in the accumulation regime and repercussions on the healthcare system in Brazil - Ligia Bahia; Mario Scheffer; Leandro Reis Tavares; Iale Falleiros Braga
Abstract: The concentration and internationalization of health plan companies in Brazil gave them a clearly financial face. Based on the need to understand the health care industry's capital accumulation patterns, the current study examines health plan companies' expansion strategies through the classification of their supply and demand characteristics by recent historical periods and an analysis of recent shareholding trends in one of the leading corporations in the Brazilian health care industry. The 1960s to 2000s witnessed changes in the scale of demands for health plans and adherence by companies to long-term accumulation strategies. Beginning in the early 21st century, changes in the shareholding structures of the largest Brazilian company, consistent with the financialization of its accumulation regime, resulted in the rapid multiplication of its capital. Deepening segmentation of the health care system in a context marked by the downturn in the national economy challenges the preservation of public subsidies for private health plans.